Sickness presenteeism explained by balancing perceived positive and negative effects - Lohaus, Daniela; Habermann, Wolfgang; Nachreiner, Malte (Frontiers in Psychology, 2022)
Within the ever-growing body of research on sickness presenteeism, studies of perceived consequences are scarce and equally rare joint consideration of beneficial and harmful effects. In this study, we investigated positive and negative effects simultaneously to determine their relationship with attendance behavior. In a cross-sectional online survey, 591 working adults in Germany rated a thoroughly developed pool of specific experienced or potential consequences of working while sick and gave an overall judgment of effects. The results show that perceptions of effects are consistent with behavior. Individuals who exhibit presenteeism do so primarily because of work-related effects. Few specific effects stand out and can largely explain attendance behavior and the overall assessment of effects. However, of the significant specific effects, none relate to the health of the individual. Consistent with assumptions of general models of work motivation and health behavior, it has been demonstrated that benefits and costs of the behavior are simultaneously weighed in the decision to engage in presenteeism or not.